Transformation towards sustainability in the construction market : Adoption of wood construction in Finland - Jussila, Jaakko (Vaasan yliopisto, 2022)
Climate change calls for actions towards sustainability on a global level. It requires nations and industries to transform the ways in which they are used to operating. The construction sector plays a vital role to expedite the transition towards sustainability due to its contribution to society and intense usage of raw material. This dissertation aims to create a better understanding of the factors that enable or hinder sustainability transition in the construction sector and housing markets. In the construction industry, wood construction is considered a solution for reducing the carbon footprint by replacing concrete construction. The role of municipalities and institutions in supporting the adoption of wood in the Finnish construction sector is a topic of specific interest for this empirical study. First, to understand the requirements for sustainability transition, this research synthesises the current scientific literature for enabling and hindering factors affecting the development of the wooden multi-story construction sector in Article I. This study implements the concept of structures of housing provision (SHP) that comprise spheres of production, consumption and exchange of houses to approach drivers and barriers for sustainability transition. Next, the role of institutional practices in the housing market is analysed in Article II from the perspective of homebuilder families in the detached home market, where wood has traditionally been used for a long time. Several institutions and governmental actions and regulations are found to affect the sustainability transformation at the level of the socio-technical landscape. Finally, Article III investigates the role of municipalities in enabling the sustainability transformation and adoption of wood in the construction sector. This dissertation presents an analytical framework that guides research and helps identify the broad and complex problems of the sustainability transition in the construction sector. As the construction sector gradually transforms towards sustainability, the benefits of the sustainability of wood and product innovations, such as efficiencies through pre-fabrication, facilitate industrial wood construction. In contrast, higher cost concerns, prejudices on quality and unfavourable institutional practices hinder the use of wood. To transform the construction industry, wood construction must be viewed not only in terms of supply mechanisms mainly connected with technological and perceived cost-efficiency benefits but also in the context of housing markets.

Ilmastonmuutos vaatii toimia kestävän kehityksen edistämiseksi maailmanlaajuisesti. Se edellyttää kansakuntia ja teollisuudenaloja muuttamaan totuttuja toimintatapojaan. Rakennusalalla on tärkeä rooli kestävän kehityksen murroksessa sen yhteiskunnallisen merkityksen ja intensiivisen raaka-aineiden käytön vuoksi. Tämän väitöskirjan tavoitteena on luoda parempi käsitys kestävän kehityksen siirtymää mahdollistavista tai estävistä tekijöistä rakennusalalla ja asuntomarkkinoilla. Puurakentaminen nähdään alalla yhtenä ratkaisuna hiilijalanjäljen pienentämiseen korvaten betonirakentamista. Empiirisessä tutkimuksessa kiinnostuksen kohteena on erityisesti kuntien ja instituutioiden rooli puun käyttöönoton tukemisessa Suomen rakennusalalla. Muutosvaatimusten ymmärtämiseksi tämän tutkimuksen artikkelissa I tehdään synteesi tieteellisestä kirjallisuudesta liittyen puukerrostalorakentamisen kehitykseen vaikuttavista mahdollistavista ja hidastavista tekijöistä. Tutkimus käyttää asuntotarjonnan rakennetta kuvaavaa mallia (ns. SHP-konsepti), joka kattaa asuntojen tuotannon, vaihdannan ja käytön, tarkastellakseen kestävän kehityksen siirtymään vaikuttavia ajureita ja esteitä. Seuraavaksi artikkelissa II analysoidaan institutionaalisten käytäntöjen roolia asuntomarkkinoilla omakotirakentajien näkökulmasta, missä puun käytöllä on pitkät perinteet. Useiden instituutioiden, valtion toimien ja sääntelyn voidaan havaita vaikuttavan kestävän kehityksen siirtymään muuttaen toimintaympäristöä. Lopuksi artikkelissa III tutkitaan kuntien roolia kestävän kehityksen muutoksen edistämisessä ja puun käyttöönotossa rakentamisessa. Väitöskirja esittelee analyyttisen viitekehyksen, joka ohjaa tutkimusta ja auttaa jäsentelemään kestävän kehityksen siirtymään liittyvää laajaa ja monimutkaista ongelmaa rakennusalalla. Rakennusalan kohdatessa kestävyysmurroksen, voidaan teollista puurakentamista edistävinä tekijöinä nähdä positiiviset tuoteominaisuudet sekä tuoteinnovaatiot, kuten esivalmistuksen kautta saavutettava rakentamisen tehokkuus. Toisaalta korkeammat kustannukset, tuotteen laatuun liittyvät ennakkoluulot, sekä epäsuotuisat institutionaaliset käytännöt hidastavat puurakentamisen kehitystä. Muutoksen aikaansaamiseksi puurakentamista on tarkasteltava laajemmin asuntomarkkinoiden kontekstissa, ei pelkästään asuntotuotantoon liittyvien teknologisten ja kustannustehokkuusnäkökulmien kautta.
Keywords: sustainable development; marketing; construction; construction industry; construction sector; timber construction; marketing communication; markets (systems); fi=Markkinointi|en=Marketing|